2008
DOI: 10.2460/ajvr.69.9.1229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a commercially available vaccine against Salmonella enterica serotype Newport on milk production, somatic cell count, and shedding of Salmonella organisms in female dairy cattle with no clinical signs of salmonellosis

Abstract: Administration of a vaccine against Salmonella Newport SRP proteins to healthy dairy cattle prior to parturition increased milk production, even in cattle without detectable shedding of Salmonella Newport or clinical signs of salmonellosis. Additional research is needed to clarify the mechanisms by which productivity was improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…This is a subunit component vaccine under conditional license, and it contains purified outer membrane proteins from S. Newport. This vaccine formulation has been shown to induce antibody production in cattle; however, no significant difference in fecal shedding of Salmonella or symptoms of disease were observed between vaccinated and unvaccinated groups (56,57). Surprisingly, it was observed that vaccinated cattle produced more milk than unvaccinated cattle, although the mechanism for this remains unclear (56).…”
Section: Vaccines Against Serogroup C Ntsmentioning
confidence: 78%
“…This is a subunit component vaccine under conditional license, and it contains purified outer membrane proteins from S. Newport. This vaccine formulation has been shown to induce antibody production in cattle; however, no significant difference in fecal shedding of Salmonella or symptoms of disease were observed between vaccinated and unvaccinated groups (56,57). Surprisingly, it was observed that vaccinated cattle produced more milk than unvaccinated cattle, although the mechanism for this remains unclear (56).…”
Section: Vaccines Against Serogroup C Ntsmentioning
confidence: 78%
“…Administration of S. Newport vaccine in cattle may further help in controlling infections in dairy herds. It will also check environmental dissemination of S. Newport by controlling faecal shedding into the environment26. No specific trends were observed in the number of the S. Newport isolates from various parts of the country.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, the economic impact of Salmonella infection is substantial and periodic multi-state outbreaks of gastroenteritis occur due to the ingestion of contaminated produce, meat, or processed foods (3). Public health measures have improved food handling and limited the dissemination of livestock waste, while vaccines have also been developed to reduce Salmonella carriage in livestock and poultry (4, 5). Despite these efforts, Salmonella infections cause over 1 million illnesses in the US every year (6).…”
Section: Introductionmentioning
confidence: 99%